Asian pop cinema Bombay to Tokyo - Server, Lee (San Francisco, California Chronicle Books, 1999)
Asian Pop Cinema is the first full-color guide to the wide-ranging films of Japan, Korea, China, Taiwan, the Philippines, Hong Kong, Southeast Asia, and India, served up with dozens of spectacular photographs, film stills, and movie posters. Outlandish animated science fiction, musical shoot 'em ups, sword epics, ghost stories, and erotic tales (sometimes all in one!)-the floodgates of Asian cinema are open and Western audiences are hungry for the dazzling thrills. Presenting the major films, the people behind them, the key elements of each genre, and interviews with John Woo and others, Lee Server brings a unique breadth of knowledge and inimitable wit to every page. From subversive camp to high-adrenaline crime thrillers, Asian Pop Cinema is a great read and exciting resource for both seasoned and uninitiated viewers.
Introduction: Once Upon a Time in the East -- Hong Kong -- John Woo Interview -- Naked Killers -- China -- Taiwan -- Japan -- Sword Theater -- Seijun Suzuki 68 Japanese Cinema Today -- Takeshi! Here! -- Anime -- Tomoaki Hosoyama Interview -- Korea -- Philippines -- Eddie Romero Speaks 108 Jose Lacaba Interview -- Southeast Asia -- India.
Includes bibliographical references (page 130) and index.
Keywords: Motion pictures -- Asia -- History; Motion picture industry -- Asia -- History